Analisis Konsep Upah dalam Perspektif Ekonomi Islam - Fata, Zainol; Paesol, Paesol (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The economy is a very important factor in people's lives. In the economy there are several problems including sources in the economy itself. In economic sources, there are two sources, namely primary sources and secondary sources. Primary primary sources are agriculture, industry, trade, human labor, while secondary sources are tourism, salaries and transportation facilities. Along with the increasing living needs of workers and families that must be met, this has an impact on wage issues. This problem arises because there are multiple perceptions of this problem, wages are very important for workers because wages are a source of morning income for workers to meet their needs, while wages for employers are production costs that must be managed as well as possible so that production activities run optimally. Wages are the price paid for the services of workers in production activities. In other words, wages are the amount paid by the company for services or services provided to the company in production activities. In Islamic economics, compensation or wages are also referred to as ujrah. Determination of workers' wages is very closely related to the principles of justice and adequacy in Islamic economics. Clarity of contracts (transactions) and commitments based on the will to do so. Based on the problems above, the author wants to discuss how the concept of fair wages is where with fair wages no party is harmed either workers or laborers and employers, so the author gives the title analysis of the concept of wages in economic perspective. The research methodology used in this research is library research with a descriptive approach. The data in this research are primary and secondary data. Based on the explanation above, it can be concluded that wages in an Islamic economic perspective, namely salary, are payments given by employers to workers for their efforts to be involved in the production process. In the process of determining wages there are principles that must be considered. The principle in determining wages is fair and proper and also employers must consider the factors in determining wages for workers. The factor that must be considered in determining wages is the contribution made by workers to the company. The higher the contribution given, the higher the wages that must be given. However, in setting wages, workers cannot demand wages above the ability of the company